Changeable graphic design to hypermodern brands - Kopp, Rudinei (2015)
In this article the logotypes of brands from the Norwegian University of Life Sciences, Nordkyn and MIT Media Lab are analyzed. These works reveal a new face of “changeable graphic design” (KOPP, 2002) and are identified as a moment characterized, by Gilles Lipovetsky term, as hypermodernity. The brands analyzed have shown the potentials and the risks that can be used to excitation of hyperconsumption and hyper-individuality.